Eﬁciência tributária municipal e seus determinantes: uma abordagem semi-paramétrica via regressão beta - Fernandes, Luiz Henrique dos Santos (2017)
The present study measures the technical tax eﬃciency of municipalities of the State of Paraíba and evaluates its determinants through a two-stage semi-parametric approach. In the ﬁrst stage, eﬃciency scores were obtained with the use of Multiple Data Envelopment Analysis(MDEA),usingdatafrom2015.ItisavariationoftheDataEnvelopmentAnalysis (DEA),whoseresultconsistsofameanofthecalculatedeﬃcienciesforeachDMU(Decision Making Unit), considering all the possibilities of choosing subsets of the variables used as inputs and outputs. This method eliminates the random choice of variables and increases the discriminatory power of the DEA. In the second stage, a variable dispersion beta regression model was used to estimate the inﬂuence of environmental variables on the tax eﬃciency of local governments. The main results showed that tax eﬃciency is directly related with the population of the municipalities, degree of ﬁnancial self-suﬃciency, value added to GDP by the industrial sector and the management transparency index. On the other hand, contributed to reduce tax eﬃciency factors such as dependence on grants from other governmental entities, per capita revenue and the Herﬁndahl concentration index applied to the municipal taxes.